Penyebab Pengembalian Klaim BPJS Rawat Inap Triwulan 1 Tahun 2024 di RSI Sultan Agung Semarang - Rizki, Julia Nur; Sari, Arum Astika; Yektiningtyastuti, Yektiningtyastuti; Suprihatin, Eni (Politeknik Negeri Jember, 2025)
The process of submitting BPJS Kesehatan reimbursement claims in hospitals often encounters issues related to administration, regulatory discrepancies, and delays, affecting patient services and satisfaction. This study aimed to analyze the factors causing the return of BPJS inpatient claims during the first quarter of 2024 and strategies to reduce claim disputes. Utilizing a descriptive research design, the study examined 282 claim files returned by BPJS Kesehatan to Sultan Agung Islamic Hospital Semarang in the first quarter of 2024. The predominant reasons for claim returns were medical aspects (242 cases), coding issues (25 cases), and administrative factors (15 cases). Coding issues included inaccurate diagnosis codes due to files containing dual diagnoses and errors by BPJS Kesehatan verifiers in reviewing submission data. Medical and administrative returns were primarily due to incomplete supporting documents, as some results were not available at the time of submission, leading to their exclusion. Submissions were still made to avoid rejection due to predetermined deadlines. Improving the claims process is essential to stabilize hospital finances and enhance service quality.